A recombinant polypeptide from velvet antler of Cervus nippon Temminck exhibits similar immunomodulatory effects as its natural counterpart. (1st November 2016) - Zha, Enhui; Dandan, Li; Bai, Xue; Zhou, Tiezhong; Li, Yongong; Shenyang, Gao; Yue, Xiqing
Abstract: Context: Velvet antler (VA) is recognized as one of the most important Chinese traditional medical herbs. To date, the immunoactivity of the single component of VA is rarely studied though its compound extracts have been well analyzed. Objective: The current study was designed to evaluate the immunomodulatory effects of a recombinant polypeptide (rVAP32) based on the VA of the sika deer by comparison with its natural counterpart (nVAP32). Materials and methods: Splenocytes proliferation and NK-cell cytotoxicity assay was evaluated by the WST-8 colorimetric method. CD4 + /CD8 +  cell subpopulations regulation was screened by the flowcytometry method and the Th1 or Th2-related cytokine production was measured by ELISA. Results: In vitro tests showed that both rVAP32 and nVAP32 could significantly stimulate splenocytes proliferation and enhance the NK-cell cytotoxicity and CD4 + /CD8 +  cell subpopulations when compared with the irrelevant peptide and blank control groups. Also, they demonstrated a significant capacity in up- and down-regulating the expression of Th1- and Th2-related cytokines, respectively. There is no statistically significant difference found between the rVAP32 tested group and nVAP32 control group. Discussion and conclusion: The results obtained herein indicate that rVAP32 has the similar immunomodulatory effects on the immune system of mice as its counterpart nVAP32 in vitro . The further test in vivo is qualified and rVAP32 is promised for developing a new biopharmaceutical product as a substitute for nVAP32.